RPORATE SOCIAL RESPONSIBILITY (CSR) BIDANG LINGKUNGAN HIDUP PADA HOTEL BINTANG LIMA DI KAWASAN PARIWISATA UBUD, KABUPATEN GIANYAR - Florencia, Olivia Grace Brigitta; Mahendra, Made Sudiana; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 2 (2016), 2016)
The negative impact of tourism accommodation development, is environmental damage. Law of the Republic of Indonesia No. 10 of 2009 on Tourism Article 26, requires owner to be responsible through environmental maintenance.Law of the Republic of Indonesia No. 40 of 2007 on Limited Liability Companies Article 74, requires each company to implement Corporate Social Responsibility (CSR).The ministry of Environment itself summarizes the CSR on environment, such as Production Profit, Eco Office, Waste Management with 3R principle (Reduce, Reuse and Recycle), Conservation of Natural Resources and Energy, Renewable Energy, Climate Change Adaptation and Environmental Education.This research aimed to analyze the effectivity of CSR programs on environmental in fivestar hotels in Ubud Region, the factors that affect the program, and its development strategy. The research used descriptive quantitative method. The method of data collection using observation, interviews, and questionnaires. Data obtained was analyzed using descriptive qualitative method, complemented with IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), and SWOT analysis.The result showed that implementation of CSR programs has not entirely been done effectively. From seven CSR programs, two programs have been categorized effective. Those two programs are Climate Change Adaptation and Environmental Education. However the program which has not run effectively is Production Profit, Eco Office, Waste Management with 3R principle (Reduce, Reuse and Recycle), Conservation of Natural Resources and Energy Renewable Energy. The main factor affecting CSR Program is organization, with score of 4.41. CSR implementation strategy, the manager continues the previous strategy that has been done. However, for the advancement of CSR programs is necessary needed revamping management, with concentration via vertical integration.
Keywords: 3R (Reduce, Reuse and Recycle); Environment; CSR Programs; SWOT